Elegies in Abo Tammam’s Poetry to Humaid Al-Tosi and his son Mohamed: A Study of Image and Rhythm - Rahim Jabr, Arkan; Farhan Atheeb, Jafar (Al-Adab Journal, 2019)
The study tackles two of the most important poetic elegies to two leaders of the Abbasid Era, Hamid Al-Tusi and his son Mohammed, written by Ali bin Jiblah Al-Akook and Abo Tammam Al-Ta'i. These two elegies are considered the eyes of Arabic poetry. The study considers the pure formations of the image and rhythm and aesthetics in these two poems, hence the title of this study.We thought that the study plan would be based on two sections after the introduction, which was entitled "Lamentations in the Abbasid Era" in which we talked about the concept of lamentation in general. Then, we briefly define the personalities of the Abbasid leaders, Hamid Al-Tusi and his son Muhammad. The first section considers the aesthetics of the picture and its images in the two poems. The research concludes with the most important findings.